(untitled) (Revista de Ciências Agroveterinárias, 2020)
Over a century ago, viticulture went from the cultivation of one species or grape variety to the cultivation of a plant composed of two genotypes: one responsible for growing the root system and the other for producing the fruit. To adapt to this new reality, a great amount of research has been done, with various studies ranging from grafting techniques to sensory analysis . Despite numerous studies on the influence of rootstocks on scion performance, many aspects of this interaction are still unclear. This study aimed to evaluate the effect that different rootstocks have on the concentration of phenolic compounds in Cabernet Sauvignon and Merlot wines produced in the Southern Highlands of Santa Catarina, Brazil, by testing rootstocks 3309C and 101-14Mgt, in addition to P1103. Experiments were conducted in the municipalities of Painel (28°01’S, 50°08’W and 1,200 m) and São Joaquim (28°14’S, 49°58’W and 1,300 m) during the 2015, 2016, and 2017 vintages to assess the concentrations of flavonoid and non-flavonoid compounds in the wines. The results indicate that different rootstocks affect the wines’ phenolic composition. The concentration of flavonoid compounds increases with rootstock 3309C, compared to the commonly used rootstock P1103, in the Southern Highlands of Santa Catarina.